Polysaccharide-Based Superporous, Superabsorbent, and Stimuli Responsive Hydrogel from Sweet Basil: A Novel Material for Sustained Drug Release. (1st January 2019) - Lodhi, Bilal Ahmad; Hussain, Muhammad Ajaz; Sher, Muhammad; Haseeb, Muhammad Tahir; Ashraf, Muhammad Umer; Hussain, Syed Zajif; Hussain, Irshad; Bukhari, Syed Nasir Abbas
Abstract : This study is carried out on polysaccharide-based hydrogel extracted from the seeds of Ocimum basilicum L. for its evaluation as a superabsorbent and stimuli responsive biomaterial for sustained release drug delivery system. O. basilicum (Syn: Basil) seed hydrogel (BSH) expressed high swelling capacity at pH 6.8 and 7.4 and deionized water. Highly reversible on-off switching (swelling-deswelling) behavior of BSH was ascertained in deionized water and ethanol, pH 7.4 and 1.2, and deionized water and normal saline. Scanning electron microscopy (SEM) of BSH has revealed macroporous structure of BSH having average pore size of 1.92 ± 3.83 μ m noted after swelling and lyophilization. BSH containing tablet formulations showed a sustained release pattern of diclofenac sodium (DS) which is dependent on the concentration of BSH. When comparing with commercially available formulation of DS, even better sustained release behavior of DS was observed in BSH-based formulation. Super case-II transport mechanism is followed by the DS release from BSH matrix tablet. Haemocompatibility studies of BSH were also performed and found it nonhaemolytic and nonthrombogenic.